Gender Equality in the Quran: An Analysis of Teun van Dijk's Critical Discourse on QS. Al-Mujadalah: 1–6 and QS. Al-Baqarah: 222 - Khoiril Waro, Mochamad Tholib (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2025)
Throughout world history, women have often been subjected to injustice, treated as property that could be traded or inherited. This condition prevailed across many civilizations, including seventh-century Arab society. Islam emerged within this context, partially accommodating prevailing traditions while also aiming to reform oppressive practices. One stark example is QS. Al-Takwir: 9, which condemns the practice of killing newborn girls. In response to such injustices, the Quran presents transformative teachings, as seen in QS. Al-Mujādalah: 1–6 and QS. Al-Baqarah: 222. These verses affirm the existence of women and challenge negative assumptions—particularly around menstruation. This study aims to examine the two verses using Teun van Dijk’s Critical Discourse Analysis, which consists of three analytical dimensions: text, social cognition, and social context. The findings show that the verses are structured through macrostructure, superstructure, and microstructure levels. Cognitively, they dismantle stigmas against women, especially those linked to menstruation. Socially, the verses were revealed in a patriarchal-agnatic society that devalued women, which influenced the development of gender-biased laws. The study concludes that these Quranic verses not only challenge structural gender injustice but also offer a framework for reclaiming women’s dignity. This research contributes to the broader discourse on gender justice in Islamic texts and demonstrates the relevance of critical discourse analysis in interpreting sacred scripture.